2022
DOI: 10.1007/s10344-022-01595-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic pelvimetry in free-ranging Eurasian lynx (Lynx lynx carpathicus) from Switzerland

Abstract: The observation of pelvic anomalies in two Eurasian lynx (subspecies Lynx lynx carpathicus) from a population reintroduced to Switzerland raised the question of the frequency of such anomalies, but no anatomical reference values were available for comparison. This study aimed at providing baseline data on the pelvic morphology of Carpathian lynx from Switzerland, and at detecting potential pelvic anomalies. Measurements of 10 pelvic parameters were performed on the radiographs of 56 lynx taken from 1997–2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, studies in the literature have demonstrated the use of height/width ratio measurements in other animals. For example, in dogs (Campos et al, 2019), cats (Celimli et al, 2008;Monteiro et al, 2013), lynxes (Morend et al, 2022) and agouti (Dasyprocta prymnolopha) bred under human care (Ferraz et al, 2022), height/width ratio measurement parameters have been derived using linear measurement values obtained from pelvimetric X-ray images. In the current study, it was observed that all length/width ratio measurements, except for the L10/L11 ratio, were significantly higher in males compared to females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies in the literature have demonstrated the use of height/width ratio measurements in other animals. For example, in dogs (Campos et al, 2019), cats (Celimli et al, 2008;Monteiro et al, 2013), lynxes (Morend et al, 2022) and agouti (Dasyprocta prymnolopha) bred under human care (Ferraz et al, 2022), height/width ratio measurement parameters have been derived using linear measurement values obtained from pelvimetric X-ray images. In the current study, it was observed that all length/width ratio measurements, except for the L10/L11 ratio, were significantly higher in males compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these obtained osteometric data offer significant insights into crucial scientific fields, including evolutionary studies, developmental research and forensic sciences (Pitakarnnop et al., 2017 ; Yilmaz & Demircioglu, 2021 ). It is especially important to examine the morphometric and morphological features of the pelvis in birds, to determine the phylogenic and allometric characteristics of bird species, to reveal their locomotor behaviour, to determine their ecological diversity, to control the healthy laying of eggs and to evaluate various congenital or acquired pathological changes related to the pelvis region (Frank et al., 2022 ; Reddy & Sivajothi, 2018 ; Rosen, 2012 ; Shatkovska et al., 2018 ). In recent years, significant advancements in computer technologies have led to the utilization of various medical imaging techniques for examining the anatomical structures of exotic pet animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the young lynx with the novel genotype, T. gondii cysts were also detected in the heart but they were not associated with inflammatory reaction. This animal was an orphan in a wildlife rescue centre that died of a severe purulent peritonitis with concomitant Yersinia pseudotuberculosis infection (Morend et al, 2022). This infection may have happened either via preying on rodents or eating contaminated food.…”
Section: Genotyping T Gondii In Lynxmentioning
confidence: 99%